1994
DOI: 10.1136/jmg.31.11.858
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of congenital heart defects in Northern Ireland (1974-1978).

Abstract: Congenital heart defects are a major congenital abnormality and are assuming increasing importance. A study was undertaken to estimate the incidence of congenital heart defects in Northern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 21 publications
(5 reference statements)
1
11
0
1
Order By: Relevance
“…Among patients with syndromes there was a 10-year-old girl with Wolfram syndrome who had pulmonary stenosis. To our knowledge, the association of Wolfram syndrome 656 with CHD had been reported in only 1 previous study.23 The 21.4% prevalence of extracardiac malformations in our data is comparable with that found in most other studies.20-22 The most frequent extracardiac anomaly in our patients was in the skeletal system followed by gastrointestinal and genitourinary systems. In the literature the most common malformations associated with CHD are those of the musculoskeletal system (8.8%).…”
Section: Resultssupporting
confidence: 94%
“…Among patients with syndromes there was a 10-year-old girl with Wolfram syndrome who had pulmonary stenosis. To our knowledge, the association of Wolfram syndrome 656 with CHD had been reported in only 1 previous study.23 The 21.4% prevalence of extracardiac malformations in our data is comparable with that found in most other studies.20-22 The most frequent extracardiac anomaly in our patients was in the skeletal system followed by gastrointestinal and genitourinary systems. In the literature the most common malformations associated with CHD are those of the musculoskeletal system (8.8%).…”
Section: Resultssupporting
confidence: 94%
“…Significant differences were observed in relation to the work of Stoll et al 12 , Hanna et al 14 , Goodship et al 15 , Grech and Gatt 3 , Meberg et al 16 , Roodpeyma et al 6 , Bosi et al 17 , Calzolari et al 18 Dadvand et al 21 and Hartman et al 22 , who found rates of 3-12.1% (p < 0.05). These were characterized by having distinct samples, both regarding the number and the clinical characteristics of their patients.…”
Section: Discussionmentioning
confidence: 72%
“…The lesion of CHD presents transposition of the great arteries, tetralogy of Fallot, hypoplastic right heart, hypoplastic left heart, single ventricle, double outlet right ventricle, truncus arteriosus, total anomalous pulmonary venous connection, atrioventricular septal defect, ventricular septal defect, patent ductus arteriosus, aortic stenosis, and so on (Hoffman and Kaplan, 2002). It is well recognized that mutations in some genes lead to CHD (Hanna et al, 1994;Hoffman and Kaplan, 2002). For instance, Tbx1 mutation causes severe outflow tract (OFT) defects.…”
Section: Introductionmentioning
confidence: 98%